La medicina della complessità BPCO e comorbidità - Gensini, Gian Franco; Fini, Massimo; Fabbri, Leonardo; nozzoli, carlo (Firenze University Press, 2010)
Medicine has coined the concept of 'disease', but individual patients frequently present complicated cases marked by the coexistence of several conditions or syndromes. The doctor needs to reflect on this complexity because, in his daily practice, he has to address and resolve it for a correct management of the patient. This is why we must, with genuine humility, seek to share a journey in which there are no major landmarks. The authority of the various colleagues who have contributed the different chapters can offer elements of guidance that are useful in a series based on the leitmotif of the cornerstone concepts of complexity. My thanks to those who have accepted this challenge, in the sincere hope that it may enrich us - even just a little and by slow degrees - with an enhanced capacity to address the daily issue of the complexity of the sick.